A study of Rift Valley fever virus in Morogoro and Arusha regions of Tanzania - serology and farmers’ perceptions - Wensman, Jonas Johansson; Lindahl, Johanna F.; Wachtmeister, N.; Torsson, E.; Gwakisa, P.S.; Kasanga, C.; Misinzo, G. (Informa UK Limited, 2015)
Introduction: Rift Valley fever (RVF) is a zoonosis primarily affecting ruminants, resulting in epidemic abortions, fever, nasal and ocular discharges, haemorrhagic diarrhoea, and a high mortality rate among young animals. Rift Valley fever virus (RVFV) is an arthropod-borne RNA virus occurring in epizootic periods associated with heavy rainfall. The last outbreak of RVF in Tanzania was in 2006–2007, resulting in severe economic losses and impaired food security due to greater number of deaths of livestock. The aim of this study was to investigate the presence of antibodies against RVFV in sheep and goats in two different regions of Tanzania during an inter-epidemic period (IEP). In addition, the perception of important diseases among livestock keepers was assessed. Material and methods: A cross-sectional serological survey was conducted in three purposively selected districts in Arusha and Morogoro regions of Tanzania. Serum samples from 354 sheep and goats were analysed in a commercial RVFV competitive ELISA. At the sampling missions, a questionnaire was used to estimate the socio-economic impact of infectious diseases. Results and discussion: In total, 8.2% of the analysed samples were seropositive to RVF, and most seropositive animals were younger than 7 years, indicating a continuous circulation of RVFV in the two regions. None of the livestock keepers mentioned RVF as an important livestock disease. Conclusions: This study confirms that RVFV is circulating at low levels in small ruminants during IEPs. In spite of recurring RVF outbreaks in Tanzania, livestock keepers seem to have a low awareness of the disease, making them poorly prepared and thus more vulnerable to future RVF outbreaks.